Hydraulic Performance Analysis for Drip Irrigation Systems Efficiency and Water Productivity - Jinan J.Alsalami; Kareem R. Almershidy; Diaa F. Hassan (International Journal of Computational and Experimental Science and Engineering, 2025)
As competition for water demand increases in all life sections, the agricultural sector has observed a gradual decrease in water consumption. To sustain or enhance agricultural productivity, innovative irrigation methods, like surface and subsurface drip irrigation systems, enhance the efficiency of water utilization compared to conventional systems. In this study investigates the impact of operating pressure and emitter spacing on the uniformity coefficient (UC), distribution uniformity (DU), and application efficiency (EA) of a surface drip irrigation system. Data revealed a nuanced relationship between these variables, with the UC achieving a peak of 92% at 150 kPa, while lower pressures (100 and 200 kPa) resulted in decreased UC values of 88% and 92%, respectively, for both 20 cm and 40 cm emitter spacing. The distribution homogeneity for the lowest quartile decreased with increasing pressure, indicating that optimal pressure is crucial for maintaining uniform water distribution. Additionally, EA reached 90% to 93% across varying pressures, highlighting an inverse relationship between drainage rate and efficiency at higher pressures. Consumptive water use for lettuce crops varied significantly across irrigation methods, with surface irrigation consuming up to 380 mm compared to 223 mm for subsurface methods, underscoring the influence of irrigation design on water management and crop efficiency. Overall, these findings suggest that careful calibration of operating pressure and emitter spacing is essential for optimizing water distribution in drip irrigation systems.